2020
DOI: 10.1038/s41598-020-76040-2
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes in human skin 32 days after death and the potential forensic significance

Abstract: To observe the histological changes in human skin within 32 days after death to explore its potential significance in forensic practice. The intact full-thickness skin and subcutaneous tissue from the sternum of eight corpses were placed in an environment of 4–6 °C for 4 h, 6 h, 12 h, 18 h, 24 h, 36 h, 48 h, 60 h, 72 h, 84 h, 96 h, 6 d, 8 d, 10 d, 12 d, 16 d, 20 d, 24 d, 28 d, and 32 d. Then, the whole layer of the skin was stained with haematoxylin & eosin. The histological morphology of the epidermis, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Cao et al (2015) observed dense neutrophil infiltration 7 days after flap elevation (Figure 3). Inflammatory infiltration was not observed in postmortem studies (Ahmed Alaa El‐Din et al, 2021; Bardale et al, 2012; Castagnoli et al, 2003; Kovarik et al, 2005; Wei et al, 2020).…”
Section: Resultsmentioning
confidence: 96%
“…Cao et al (2015) observed dense neutrophil infiltration 7 days after flap elevation (Figure 3). Inflammatory infiltration was not observed in postmortem studies (Ahmed Alaa El‐Din et al, 2021; Bardale et al, 2012; Castagnoli et al, 2003; Kovarik et al, 2005; Wei et al, 2020).…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, the current study was also conducted to evaluate the expressions of lncFAO, which were strongly associated with healing sequences, especially inflammation resolution and tissue repair [ 5 , 20 , 32 ]. We identified its specificity in wound dating estimation and stability during early PMIs (up to 24 h).…”
Section: Discussionmentioning
confidence: 99%
“…3). It is thought that the individual cells in mammalian tissues die gradually over time suggesting gradual reduction in stem cell pool in postmortem tissues (Wei et al 2020). The time taken to have complete death of all cells in a tissue may depend upon several variables such as environmental temperature, chemical or radiation exposure, humidity, age, and health of an animal.…”
Section: Discussionmentioning
confidence: 99%
“…Collection of tissues from live animals present an ethical issue, however, accidentally dead animals (domestic or wild) and slaughterhouse is a potential alternate to harvest tissues. Death, however, brings successive cessation of metabolic activities and ultimately carcass decomposition compromising nuclear DNA integrity of the individual cells in postmortem tissues (7) and ultimately cell death. Cold storage of biological tissues has been shown to delay decomposition and cell death (8).…”
Section: Introductionmentioning
confidence: 99%